CFD modeling of the fluid-dynamics present in the charging process of a dual-fuel (diesel-NG/diesel-hydrogen) engine (2022)
ABSTRACT : In this work was made a CFD cold flow simulation of a dual fuel diesel-natural gas (NG)/hydrogen engine. The simulation was made aimed to characterize and understand the flow behaviour in-cylinder and the effect of a dual gaseous fuel addition to the flow patterns and the main flow values that affect how combustion process is realized in the engine. Main flow patterns as swirl and tumble were analyzed with main fuel energy share (of NG and hydrogen) as parameter. The model was realised in Ansys Workbench as pre-processor and Ansys Fluent as solver. In order to set the model, it was made a general literature review to define the models and sub-models used in internal combustion engines cold flow simulations. Then, a recompilation of most important engine data (4JH1-TC) was executed. With the engine data, a 3D solid was constructed to feed the pre-processor. Consequently, the geometry was meshed in three different meshes with the aim of capture the grid independence. After grid independence, the model was fully established and the main simulations were carry out. Results show as a trend an increasing in the flow patterns when substitution/enrichment levels were increased. An hypothetical response to this influence is the physical properties of the hydrogen and NG, gases that are lighter than the air and with higher molecular diffusivity (hydrogen), thus having bigger disorder in the motion in-cylinder enhancing the flow movement intensity. In the meanwhile study, a parallel study was carried out aiming to select the best turbulence model for the type of simulation realized (cold flow simulation). Finally, some engineering applications for the model were presented, exploring fundamental aspects of internal combustion engines for the application of the model.